Les prix de l’assurance habitation reflètent-ils un marché de concurrence parfaite ? - Outreville, J.-François; Bédard, Eric; Brochu, France (Assurances, 1984)
Is home insurance subject to a limited or total competition? With the help of his students, Mr. J.-François Outreville looks at this question and uses mathematical formulas to arrive at an interesting theoretical conclusion.